Depiction of Gender Roles & Femininity in Cinematic Adaption of Louisa May Alcott’s Novel Little Women by Greta Gerwig - Haddad Nurris; Diah Tyahaya Iman (English Study Program, Faculty of Humanities, Universitas Andalas, Padang, 2025)
This study aims to compare two works in different mediums: a novel titled Little Women, authored by Louisa May Alcott in 1868, and its film adaptation of the same title, directed by Greta Gerwig in 2019. This study explores how Greta Gerwig transformed gender roles and femininity in Little Women’s novel into a film version. This study employs the fidelity theory offered by James M. Welsh and the adaptation theory proposed by Linda Hutcheon. Qualitative analysis and library research are used as research methods in this study. The results revealed that the gender roles in the film adaptation had been portrayed with some changes, to focus more on their struggles to obtain their dreams and less romantic portrayal. The writers argue that femininity in the novel is depicted with a more modern sense of femininity and more aligned with modern feminist ideas.